EPIDEMIOLOGICAL PROFILE OF PATIENTS UNDERGOING INVASIVE MECHANICAL VENTILATION IN INTENSIVE CARE UNITS FROM MACEIÓ. (Fiep Bulletin - online, 2012)
The ICU`s has been defined as a health service for people who are in a serious situation, but they have a really good chance to recover, these people would be benefit by an clinic observation more detailed and an invasive treatment. The aim of this study was to identify what type of patient is subjected to invasive mechanical ventilation, to check the most frequent pathologies that lead patients to make use of it, and register the differences in private hospitals, regarding the patient profiles mechanically ventilated.
Keywords: Epidemiologic Profile; ICU; invasive mechanical ventilation; respiratory failure.